LncRNA PTS-1 Protects Against Osteoarthritis Through the miR-8085/E2F2 Axis - Ma C; Chen Q; Wei YF; Chen SW; Liu H; Xin F; Ren YX (Journal of Inflammation Research)
Cheng Ma,1,* Qi Chen,2,* Yi-Fan Wei,1,* Shu-Wen Chen,3 Huan Liu,4 Feng Xin,5 Yong-Xin Ren1 1Department of Orthopaedics, The First Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 2Department of Orthopaedics, The Affiliated Changzhou No.2 People’s Hospital of Nanjing Medical University, Changzhou, Jiangsu, People’s Republic of China; 3Department of Clinical College, The First Clinical School of Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 4Department of Orthopaedics, The Affiliated Huai’an No.1 People’s Hospital of Nanjing Medical University, Huai’an, Jiangsu, People’s Republic of China; 5Department of Orthopaedics, Xuzhou Cancer Hospital, Xuzhou, Jiangsu, 221005, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feng Xin; Yong-Xin Ren, Email 925866554@qq.com; renyongxinjsph@163.comBackground: Osteoarthritis (OA) is a leading cause of pain, disability, and reduced mobility worldwide, characterized by metabolic imbalances in chondrocytes, extracellular matrix (ECM), and subchondral bone. Emerging evidence highlights the critical role of long non-coding RNAs (lncRNAs) in OA pathogenesis. This study focuses on lncRNA PTS-1, a novel lncRNA, to explore its function and regulatory mechanisms in OA progression.Methods: The expression profile of lncRNAs was assessed using RNA sequencing and qRT-PCR. The expression of lnc-PTS-1 was further validated by qRT-PCR in degenerated cartilage tissues, degenerative primary chondrocytes, and IL-1β-treated C28/I2 cells. Cell viability, proliferation, and apoptosis rates, along with the mRNA and protein levels of apoptosis-related markers (cleaved Caspase 3, cleaved Caspase 9, Bcl-2, Bax), ECM metabolism markers (MMP-3, MMP-13, aggrecan, collagen II), and inflammation-related markers (IL-1β, IL-6, TNF-α) were evaluated using Cell Counting Kit-8, Toluidine Blue staining, Alcian Blue staining, flow cytometry, qRT-PCR, immunofluorescence, and Western Blot. The interaction between miR-8085 and lnc-PTS-1 or E2F2 was investigated through dual luciferase reporter assays and RNA immunoprecipitation (RIP) analyses.Results: Lnc-PTS-1 expression was significantly downregulated in degenerated cartilage tissues, IL-1β-induced degenerative primary chondrocytes and C28/I2 cells. Functional experiments showed that lnc-PTS-1 knockdown aggravated IL-1β-induced ECM degradation, chondrocyte apoptosis, and inflammation, while its overexpression provided protective effects. Mechanistically, lnc-PTS-1 acted as a competing endogenous RNA (ceRNA) by sponging miR-8085, thereby upregulating E2F2 expression. Notably, miR-8085 upregulation diminished the protective effects of lnc-PTS-1 on ECM degradation, apoptosis, and inflammation, while E2F2 upregulation partially alleviated IL-1β-induced damage. However, these mitigating effects were reversed by miR-8085 overexpression.Conclusion: These findings identify lnc-PTS-1/miR-8085/E2F2 axis as a novel regulatory mechanism in OA pathogenesis, providing theoretical basis and experimental evidence for the potential clinical application of new lncRNA molecules in the treatment of OA.Keywords: osteoarthritis, long non-coding RNA PTS-1, E2F2, miR-8085